ANALISIS PENANGKAPAN DAN PERDAGANGAN TRENGGILING JAWA - Mariana Takandjandji; Reny Sawitri (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2016)
Conservation status ofsunda pangolin (Manis javanica , 1822) is listed as protected species. However, this Desmarestspecies is threatened by illegal trade. The pangolin is a scaly and toothless mammal. The main foods ofthis species are ants and termites. Some people believe that sunda pangolin is beneficial to the health so that trigger of very high commercial value. The research objectives were to determine the public perception on its utilization related to poaching and illegal trade and also to estimate the number ofillegal trade during the period of 2002 to 2015. Snowball and purposive sampling techniques were carried out in data collecting by using questionnaire to respondents as key informants. Communities perceived that Sunda pangolin have a high economic value ofwildlife that can increase people's income (40%) and can be poached ifthere is a chance (52%). Over the last fourteen years, as much as 319,460 of sunda pangolins were exported. To address these issues can be done through improving regulation in line with international regulations such as CITES, capacity building of rangers and investigators in related to online trading and use of electronic evidence, increasing public awareness, DNA forensics, as well as cooperation with related parties